Extraction of DNA from honey and its amplification by PCR for botanical identification - Jain,Sona Arun (2013)
The physiochemical and biological properties of honey are directly associated to its floral origin. Some current commonly used methods for identification of botanical origin of honey involve palynological analysis, chromatographic methods, or direct observation of the bee behavior. However, these methods can be less sensitive and time consuming. DNA-based methods have become popular due to their simplicity, quickness, and reliability. The main objective of this research is to introduce a protocol for the extraction of DNA from honey and demonstrate that the molecular analysis of the extracted DNA can be used for its botanical identification. The original CTAB-based protocol for the extraction of DNA from plants was modified and used in the DNA extraction from honey. DNA extraction was carried out from different honey samples with similar results in each replication. The extracted DNA was amplified by PCR using plant specific primers, confirming that the DNA extracted using the modified protocol is of plant origin and has good quality for analysis of PCR products and that it can be used for botanical identification of honey.